2020
DOI: 10.3390/diagnostics11010038
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Ischemic and Hemorrhagic Strokes in Functional Outcome at Discharge from an Intensive Rehabilitation Hospital

Abstract: Comparison studies on recovery outcomes in ischemic (IS) and hemorrhagic strokes (HS) have yielded mixed results. In this retrospective observational study of consecutive IS and HS patients, we aimed at evaluating functional outcomes at discharge from an intensive rehabilitation hospital, comparing IS vs. HS, analyzing possible predictors. Modified Rankin Scale (mRS) at discharge was the main outcome. Out of the 229 patients included (mean age 72.9 ± 13.9 years, 48% males), 81 had HS (35%). Compared with IS (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 19 publications
5
26
0
1
Order By: Relevance
“…As we did not have a stroke unit in our hospital, young patients with ischemic strokes entered the neurology service, while elderly people or those with a hemorrhagic cause were referred to other services or units. It seems logical that stays in our physical medicine and rehabilitation service were longer than in other studies in as much as we received patients early in the acute/sub-acute phase [ 10 , 23 , 24 ]. This is confirmed by analysing the significant degree of disability with which they entered our service in comparison to other published studies.…”
Section: Discussionmentioning
confidence: 99%
“…As we did not have a stroke unit in our hospital, young patients with ischemic strokes entered the neurology service, while elderly people or those with a hemorrhagic cause were referred to other services or units. It seems logical that stays in our physical medicine and rehabilitation service were longer than in other studies in as much as we received patients early in the acute/sub-acute phase [ 10 , 23 , 24 ]. This is confirmed by analysing the significant degree of disability with which they entered our service in comparison to other published studies.…”
Section: Discussionmentioning
confidence: 99%
“…The median FIM gain for ICH patients tended to be higher than CI patients (ICH 27 vs. CI 21, p = 0.05). Only the ICH group achieved FIM-G exceeding the MCID threshold for acute stroke ∆22, [23] compared to CI patients. Greater FIM gain in ICH patients was consistent with the local study by Ng et al [17].…”
Section: Discussionmentioning
confidence: 91%
“…Chu et al postulated that participating in rehabilitation aids in reorganization of the neural network, increases neuroplasticity and angiogenesis, and augments hematoma and toxic blood product clearance in ICH patients [18]. It was also noted in a study by Salvadori et al that better functional outcomes in ICH vs. CI patients were seen in studies conducted in specialized rehabilitation settings, while worse or equivocal outcomes were seen in studies conducted in community or acute hospital settings [23]. Ng et al also reported that all patients, regardless of their stroke subtypes, made clinically significant functional gains on completion of inpatient rehabilitation [17].…”
Section: Discussionmentioning
confidence: 99%
“… 9 ) Salvadori et al revealed age and initial stroke severity as the main prognostic factors of functional recovery. 10 ) Jørgensen et al reported initial stroke severity as the all-important prognostic factor. 11 ) In summary, patients with initial neurological severity tended to have a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%